DERMATOGLIFI UJUNG JARI DAN TELAPAK TANGAN PENDERITA TUNANETRA DI PANTI SOSIAL BINA NETRA (PSBN) TUAH SAKATO PADANG - Sari, Weni Novita (Pendidikan Biologi, 2014)
Dermatoglyphics is a theory of knowledge based on the epidermal or ridge skill on the skin surface. This study arms to investigate the characteristic dermatoglyphics fingertips and palms in PSBN Tuah Sakato Padang blind patients. This study used a purposive sampling method for random sampling group for the visually impaired and normal group. From the data shows that the percentage of fingerprint patterns between visually impaired and normal groups. In which the percentage of fingerprint patterns of the largest blind group 40,5% radial loops . While the normal group 24% radial loops. The test statistic is chi-square test showed that fingerprint patterns visually impaired group and the normal group there is a noticeable difference. Based on the statistical test is test number tendrils fingertips t-student patients who do not suffer from blind and visually impaired are not significantly different. Percentage frequency palms spiraling patterns in which the percentage of visually impaired group =55,5% and I4=60%, while the normal group =12,5% I4=80% and H=2,5% and the big blind atd angel and normal patients were not significantly different.